Tietz textbook of clinical chemistry and molecular diagnostics. - Ashwood, Edward R., 1953-; Bruns, David E., 1941-; Burtis, Carl A., ....- (St. Louis (Mo.) : Saunders, 2012)
As the definitive reference for clinical chemistry, Tietz Textbook of Clinical Chemistry and Molecular Diagnostics, 5th Edition offers the most current and authoritative guidance on selecting, performing, and evaluating results of new and established laboratory tests. Up-to-date encyclopedic coverage details everything you need to know, including: analytical criteria for the medical usefulness of laboratory procedures; new approaches for establishing reference ranges; variables that affect tests and results; the impact of modern analytical tools on lab management and costs; and applications of statistical methods. In addition to updated content throughout, this two-color edition also features a new chapter on hemostasis and the latest advances in molecular diagnostics.
Keywords: Laboratoriumdiagnostiek